Human Resource Audit as an Instrument of Performance Measurement and Strategic Decision Making - Fresa Dwi juniar sofalina (Maneggio, 2025)
This study aims to analyze the role of human resources audit (HR Audit) as an instrument in performance measurement and strategic decision making in organizations with a quantitative approach. The method used is a survey involving questionnaires distributed to employees and HR managers in several companies to measure the influence of HR Audit on organizational performance as well as strategic decisions taken. The collected Data were analyzed using descriptive and inferential statistical techniques to examine the relationship between HR Audit implementation and performance measurement, as well as its impact on the quality of strategic decision-making. The results showed that the implementation of a consistent and structured HR Audit has a significant effect on improving the performance of employees and organizations, as well as a significant contribution in improving strategic decision-making. More objective performance measurement through HR audits allows companies to identify areas that need improvement, thereby improving operational efficiency and competitiveness. In conclusion, HR Audit proved to be an effective tool in supporting more informed strategic decision making and improved overall organizational performance. This study emphasizes the importance of the use of HR Audit in the managerial process to improve the effectiveness and sustainability of the organization.